2014
DOI: 10.6000/1927-5951.2014.04.01.8
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Magnesium Salts – A Review

Abstract: Background: Magnesium supplementation is of value in several different medical disorders. Several kinds of Mg-salts are commercially available. Purpose: This review evaluates their bioavailability criteria such as solubility, urinary excretion, and plasma levels of magnesium from studies of different Mg-salts. Conclusion: Although methodology differences were large, the results consistently demonstrate a better bioavailability for Mg-citrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
2
19
0
1
Order By: Relevance
“…The present results further support the general scientific opinion that the inorganic Mg compound Mg oxide is not as easily absorbable as organic Mg compounds [24]. Several studies showed that organic Mg compounds, such as Mg aspartate-hydrochloride or Mg lactate, generally have a higher bioavailability than Mg oxide [12,13].…”
Section: Discussionsupporting
confidence: 87%
“…The present results further support the general scientific opinion that the inorganic Mg compound Mg oxide is not as easily absorbable as organic Mg compounds [24]. Several studies showed that organic Mg compounds, such as Mg aspartate-hydrochloride or Mg lactate, generally have a higher bioavailability than Mg oxide [12,13].…”
Section: Discussionsupporting
confidence: 87%
“…3) Although we took into account the elemental magnesium dose prescribed, the bioavailability of magnesium salts is still important issue that could introduce bias, because organic salts have a higher solubility, absorption, and therefore, bioavailability than inorganic salts [67].…”
Section: Discussionmentioning
confidence: 99%
“…Although in preclinical and clinical studies it was observed that organic Mg salts (e.g. acetate, pidolate, citrate, gluconate, lactate, aspartate) are better sources of Mg itself than inorganic Mg salts (MgO, MgCl 2 , MgSO 4 , MgCO 3 ) [20]; and a small analgesic inactive dose of two organic salts (i.e. Mg lactate dihydrate and hydroaspartate) and one inorganic salt (i.e.…”
Section: Discussionmentioning
confidence: 99%